2014
DOI: 10.1088/0031-9155/59/21/6487
|View full text |Cite
|
Sign up to set email alerts
|

A breast-specific, negligible-dose scatter correction technique for dedicated cone-beam breast CT: a physics-based approach to improve Hounsfield Unit accuracy

Abstract: The purpose of this research was to develop a method to correct the cupping artifact caused from x-ray scattering and to achieve consistent Hounsfield Unit (HU) values of breast tissues for a dedicated breast CT (bCT) system. The use of a beam passing array (BPA) composed of parallel-holes has been previously proposed for scatter correction in various imaging applications. In this study, we first verified the efficacy and accuracy using BPA to measure the scatter signal on a cone-beam bCT system. A systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…3), and compared to the Yang et al reported values [27]. Yang et al reported that the measured HU values of 100% glandular, 50:50 glandular: adipose and 100% adipose tissue were approximately 46, −35 HU, and −94 HU, respectively; note that the variability of their system was not reported.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…3), and compared to the Yang et al reported values [27]. Yang et al reported that the measured HU values of 100% glandular, 50:50 glandular: adipose and 100% adipose tissue were approximately 46, −35 HU, and −94 HU, respectively; note that the variability of their system was not reported.…”
Section: Resultsmentioning
confidence: 96%
“…Yang et al [27] have characterized the performance of a new scatter correction method for BCT, wherein they also investigate HU accuracy for different breast tissue compositions. Although those HU values are specific to their BCT system, the individual HU values can be used for comparison with the water:methanol HU values measured on our system (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue segmentation and subtraction can isolate the tumor's outer shell for precise characterization of how the tumor changes over time as compared to its previous appearance. Improvements in the breast CT's spatial resolution [30,31] and contrast resolution [32] are foreseeable and will provide larger databases and an even greater importance of image optimization, possibly with AR/VR imaging.…”
Section: Future Role Of Ar/vr In Diagnostic Medical Imagingmentioning
confidence: 99%
“…Researchers have developed similar methods in CBBCT for image quality improvement. For example, Ioannis [3] and Yang [4] proposed to insert a beam stop array between the x-ray source and the object for scatter measurement, in a scan additional to the conventional CBBCT scan. Chen [5] demonstrated accurate scatter estimation via Monte Carlo (MC) simulation and thus showed the potential of MC-based scatter correction at the cost of intensive computation.…”
Section: Introductionmentioning
confidence: 99%